Relationships among muscle characteristics and rowing performance in collegiate crew members - Nabavizadeh, O.; Herda, A. A. (The Sport Journal, 2022)
Purpose: The purpose of this study was to explore the relationships among measurements of muscle quality and rowing performance in college-aged club rowers. Methods: Ten men and women (mean ± SD: age: 22.1 ± 4.0 years; ht: 180.5 ± 8.3 cm; wt: 79.0 ± 13.5 kg) volunteered to participate in this study. Ultrasound images were collected at 50% thigh length in a transverse plane to quantify muscle size. The sum cross-sectional area (mCSA) of these muscles was reported. Bioelectrical impedance analysis (BIA) was conducted to predict fat-free mass (FFM) and estimate total leg lean mass. One-repetition maximum leg press (LPMAX) was recorded as well as vertical jump (VJHT; cm). Lastly, participants completed a 2,000m time trial on the rowing ergometer, where the 500m average split was used in analyses. Pearson`s product moment correlations were calculated across all variables and backwards stepwise linear regression was completed using VJHT, LPMAX, FFM, and mCSA as possible predictors of 500m performance. Results: The correlations coefficients among recorded variables were all very high and significant (r = 0.867-0.950; p = 0.001-0.04). The regression analysis indicated VJHT was a significant predictor of 500m time trial performance (R2=0.903; p<0.05). Conclusions: Although rowing may often be considered an endurance sport, the single best predictor of and the strongest correlation to time trial performance is vertical jump height as an index of power. Applications in Sport: Emphasis on plyometric training may serve as one of the most important aspects of athlete development beyond rowing form and mechanics, more so than strength or hypertrophy in collegiate rowers.